Analysis of Betawi Cultural Values on Accounting Decision Making in MSMEs in Kota Bambu Selatan District, Jakarta - Nurmala Savitri; Muhammad Aras Prabowo; Nur Ain Ayunni Sabri (Trescode Green Organization, 2025)
The aim of this research is to find out how Betawi cultural values ​​influence accounting decisions made by MSMEs in Jakarta. Integrity (Honest), Religiosity (Religious or Pious), Objectivity (Fair), Mutual Cooperation (Devotional Work), Courage (Brave), and Politeness (Manners) are values ​​in Betawi culture. The people of Kota Bambu Selatan believe that these values ​​influence their actions and business practices. To conduct this research, we collected literature and interviews with owners of small and medium enterprises (MSMEs) in the Jakarta area who have a Betawi cultural background. The research results show that Betawi cultural values ​​significantly influence accounting decision making; MSMEs tend to prioritize transparency and honesty in arranging their finances, and they strongly believe in social responsibility. Collective decision making and teamwork are other examples of the value of mutual cooperation. Researchers found that understanding and applying local cultural values ​​can improve the quality of accounting decisions made by MSMEs. They also show how important it is to incorporate cultural values ​​into accounting education and training for MSME players.